Impact of wired broadband services development on operators' IP network evolution - Lili TANG; Ming NIE; Ning ZHANG (Dianxin kexue)
With the development of wired broadband services,new requirements on the carrying ability of network was put forward by video-dominated services.The demand on bandwidth and network quality of wired broadband traffic grooming was analyzed,and a feasible network evolution solution were presented from the perspective of multicast technology application,BRAS and CDN deployment,backbone network architecture evolution and other point of view.